A fiscal outlook for Poland: Update 2014. Background paper prepared for the World Bank's Country Economic Memorandum (CEM) for Poland - Janusz Jabłonowski; Christoph Müller (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2014)
Poland faces one of the most rapidly ageing population in Europe. The old age dependency ratio is expected to triple until 2060. Against this background, our paper examines the sustainability of Polish public finances and its isolated subsystems. We consider the profound recent reforms including the transfer of 2nd pillar pension obligations to the general government in 2014. Furthermore, we extend our previous computations (Jablonowski et al., 2011) by using data from household budget surveys as well as large pension contributors' and tax payers' databases. Our results show that the pension reforms enacted since 2011 improve the long-term stability of public finances. A risk for fiscal sustainability represents, however, the public health care system which may be severely challenged by the ageing process and a continuing excess cost growth. We assess a number of health reforms including co-payments and a shift to tax financing which have the potential to stabilize the public health care system.
Keywords: H50; H55; H60; H68; J10; H3; 330